A Cognitive Style Perspective to Handheld Devices: Customization vs. Personalization - Chen-Wei Hsieh (Athabasca University Press, 2016)
Handheld devices are widely applied to support open and distributed learning, where students are diverse. On the other hand, customization and personalization can be applied to accommodate students’ diversities. However, paucity of research compares the effects of customization and personalization in the context of handheld devices. To this end, we developed a customized digital learning system (CDLS) and personalized digital learning system (PDLS), which were implemented on the handheld devices and tailored to the needs of students with diverse cognitive styles. Furthermore, we conducted two empirical studies to examine the effects of cognitive styles on the use of the CDLS and PDLS. More specifically, Study 1 identified the preferences of each cognitive style group, which were employed to develop the PDLS in Study 2, which investigated how students with different cognitive styles react to the CDLS and the PDLS.  The results from these two studies showed that student in the CDLS and those in the PDLS obtained similar task scores and post-test scores. However, Serialists with the PDLS could more efficiently complete the tasks than those with CDLS. Additionally, Holists more positively perceived the PDLS than Serialists.